FACTORS ASSOCIATED TO EARLY INTRODUCTION OF COMPLEMENTARY FEEDING : META ANALYSIS STUDY IN INDONESIA - Azrimaidaliza Azrimaidaliza; Helmizar Helmizar; Chica Nahdatul Huda (International Journal of Health Science & Medical Research, 2023)
More than 40% of mothers in the world, including Indonesia, have given food other than breast milk when the baby is less than six months old. Various factors can lead to early complementary feeding in Indonesia. The novelty of this research is because it examines about factors associated with early complementary feeding in Indonesia. This study aimed to determine the factors associated with early complementary feeding in Indonesia. This study used a quantitative design and meta-analytical analysis technique. Articles were included in this study, which were searched using Google Scholar, Garuda Portal, and ISJD databases. A total of 1,157 identification articles, with keywords ((early complementary feeding, complementary feeding administration in infants aged 0-6 months, early breastfeeding or prelacteal feeding) and (factors or factors related to, risk factors, knowledge) mother or education level, family support, support health workers, promotion of complementary feeding products, baby porridge, baby biscuits, formula or culture) and (cross sectional or case control) and (region in Indonesia)). The search was performed using the Indonesian language. Fifteen articles were systematically reviewed and included in this meta-analysis.  There is no significant relationship between maternal education level, family support, support from health workers and culture with early complementary feeding in Indonesia. Mothers’ low knowledge of exclusive breastfeeding and complementary feeding is one of the factors contributing to early complementary feeding in Indonesia. Conclusion is Mother which low knowledge is at risk 2.63 times to have early introduction of complementary feeding for baby (95% Cl; 1.14-6.09).